Thermal and mechanical transient behaviour of steel doors installed in non-load-bearing partition wall assemblies during exposure to the standard fire test - Nassif, A.; Yoshitake, I.; Vimonsatit, Vanissorn (John Wiley and Sons Ltd., 2016)
In this paper, the authors present experimental results and observations of four full-scale standard fire tests on single-leaf steel doors and steel frames installed in 3×3m non-load-bearing partition walls. Three full-scale fire tests were performed on steel doors installed in lightweight partition walls constructed by using steel C-section studs with gypsum boards fixed on both sides. Two lightweight walls incorporated Rockwool cavity insulation, while the third lightweight wall was constructed without cavity insulation. The fourth fire test involved a steel door installed in a masonry partition wall. While the steel door leaf and door frames were identical in all four full-scale tests, only the steel door installed in the masonry wall achieved the desired fire resistance rating of 30min. The integrity criterion for fire resistance was determined for the scenario when the door opened away from the furnace. The duration of fire resistance according to the integrity criterion was found to be 38, 25 and 19min for the same door when installed in masonry wall, uninsulated lightweight wall and insulated lightweight wall respectively. For the thermal insulation criterion of fire resistance, the scenario of the door opening into the fire was found to be the most onerous.